Electrochemical Detection of Prostate Cancer Biomarker PCA3 Using Specific RNA-Based Aptamer Labelled with Ferrocene - Alexei Nabok; Hisham Abu-Ali; Sarra Takita; David P. Smith (Chemosensors, 2021)
This paper reports on a feasibility study of electrochemical in-vitro detection of prostate cancer biomarker PCA3 (prostate cancer antigen 3) in direct assay with specific RNA aptamer labelled with a redox group (ferrocene) and immobilized on a screen-printed gold electrode surface. The cyclic voltammograms and electrochemical impedance spectroscopy methods yield encouraging results on the detection of PCA3 in a range of concentrations from 1 μg/mL down to 0.1 ng/mL in buffer solutions. Both anodic and cathodic current values in cyclic voltammograms measurements and charge transfer resistance values in electrochemical impedance spectroscopy experiments correlate with the PCA3 concentration in the sample. Kinetics studies of the binding of the PCA3 to our aptamer demonstrated high specificity of the reaction with a characteristic affinity constant of approximately <semantics>4·10−10</semantics> molar. The results of this work provide a background for the future development of novel, highly sensitive and cost-effective diagnostic methodologies for prostate cancer detection.